Modeling Calving Front Dynamics Using a Level-set Method: Application to Jakobshavn Isbræ, West Greenland - Bondzio, Johannes; Seroussi, Helene; Morlighem, Mathieu; Kleiner, Thomas; Rückamp, Martin; Larour, Eric; Humbert, Angelika (2016)
Recent observations highlight the influence of the calving front position on tidewater glaciers. Here, we present the theoretical and technical framework for a level-set method (LSM), which is now implemented into the Ice Sheet System Model. The LSM proves to be a robust tool to implicitly represent a dynamically evolving calving front in an Eulerian approach. We apply this method to a 3D thermodynamically coupled model of Jakobshavn Isbræ, West Greenland.